CLASSICAL NAHWU SCIENCE: THE THEORY OF I'RAB, 'AMIL, AND A CRITICAL REVIEW OF THE BASRAH AND KUFA MODELS - Erni Nurjaya; Ahmad Dani; Hamzah (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This research discusses the concepts of i’rab and ‘amil in Arabic grammar and examines the methodological differences between the Basra and Kufa schools as the two primary streams in the construction of nahwu (syntax). I’rab is understood as the changes in the vowels at the end of words influenced by the presence of an ‘amil (governor) and the word's position within the sentence structure, thus playing a vital role in preserving meaning and syntactic order in the Arabic language. This study employs a qualitative approach with a library research method, tracing primary sources from the works of classical scholars and secondary sources from modern studies. Data analysis was conducted using content and comparative analysis methods to identify the epistemological characteristics of both schools. The results of the study show that the Basra school is prescriptive, rational, and selective regarding linguistic sources, whereas the Kufa school is more descriptive, flexible, and open to various speech patterns, including those considered syadz (irregular). These differing approaches impact how both schools understand and formulate the rules of i’rab and ‘amil. This study concludes that both schools provided distinct yet complementary contributions to the development of Arabic nahwu, where Basra played a role in theoretical standardization and Kufa contributed to the preservation of linguistic reality. These findings emphasize that the understanding of i’rab is not only related to grammatical aspects but is also supported by historical and epistemological perspectives within the scientific tradition of the Arabic language.